2016
DOI: 10.1111/ddg.12989
|View full text |Cite
|
Sign up to set email alerts
|

Nail involvement can predict enthesopathy in patients with psoriasis

Abstract: Clinical evidence of onychopathy may be the clue to an early diagnosis of enthesopathy in psoriasis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 13 publications
4
28
0
Order By: Relevance
“…In another study, Castellanos-González et al conducted US examinations in patients with Ps and found the presence of enthesopathy in 31% of patients with onycholysis. The frequency of changes in the digital extensor tendon or its attachment in the DIP joint of digits with nail involvement was nearly 83% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Castellanos-González et al conducted US examinations in patients with Ps and found the presence of enthesopathy in 31% of patients with onycholysis. The frequency of changes in the digital extensor tendon or its attachment in the DIP joint of digits with nail involvement was nearly 83% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nail bed is also graded 0–4 for onycholysis, splinter hemorrhages, subungual hyperkeratosis and oil drops. There is a significant correlation between target NAPSI score and evidence of enthesopathy in the course of PsA [14]. …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Castellanos-Gonzalez et al [ 15 ] showed that the clinical presence of onychopathy is a predictor of US enthesitis at DIP level in patients with psoriasis.…”
mentioning
confidence: 99%
“…On the other hand, data related to the utility of US to predict the progress of the disease are emerging [ 5 , 10 , 15 ]. US has shown that the central inflammatory change in PsA takes place in the entheseal compartment.…”
mentioning
confidence: 99%